(untitled) (Environment & Health, 2019)
The purpose of the work is to study the awareness and consciousness of students of higher educational institutions of various profiles in healthy lifestyle and a threat to health of risk factors for the development of non-infectious diseases, in particular, nutrition. Materials and methods: a sociological survey was conducted among students of higher educational institutions of Ukraine on the levels of awareness and prevalence of certain factors in the development of non-infectious diseases. The study involved 430 students of the Kyiv National University of Trade and Economics and 217 students of Sumy State Pedagogical University. Used methods: sociological, statistical. Results: A high level of students’ awareness of the main factors in the development of non-infectious diseases, in particular nutrition, was established. However, their awareness does not lead them to realize the threat to the health of these factors. The prevalence of negative factors in students’ eating behavior, such as the consumption of excessive amounts of sugar, salt, carbonated drinks, spreads and margarines, lack of fresh vegetables and fruits in the diet, etc., was studied. It shows a significant difference in the indicators of the eating behavior of students from different universities. Conclusion: the need for further development and improvement of information and training programs for students to improve their awareness and awareness of the risk factors for the development of non-infectious diseases has been substantiated.